Microbial Strategies for the Degradation of Organophosphates: A Sustainable Approach to Pollution Control - Santiago, Denny Noriel; Mendoza, Rose Ann; Thao, Nguyen Thi Thanh; Kristanti, Risky Ayu (Tecno Scientifica Publishing, 2025)
Organophosphates (OPs) were synthetic chemical compounds that had been applied in household products as well as in agricultural and industrial sectors. Although OPs had proven effective, particularly as pesticide ingredients, their persistence in the environment had raised concerns regarding impacts on ecosystems, the environment, and human health. This study addressed the occurrences and negative impacts of OPs, with a primary focus on microbial degradation as a bioremediation strategy. While various degradation methods had been developed, microbial degradation showed strong potential as a sustainable and cost-effective approach. This review aimed to examine the mechanisms, benefits, and limitations of microbial degradation of OPs, thereby addressing the knowledge gap related to its real-world applications. Microbial degradation involved the use of bacteria capable of breaking down OPs through enzyme production, transforming them into less harmful substances. In comparison with chemical or physical methods, microbial degradation was more environmentally friendly, cost-effective, and adaptable to surrounding conditions. By synthesizing findings from previous studies, the report highlighted both the strengths and shortcomings of microbial degradation in mitigating OPs contamination. The findings underscored its promise as a viable solution, while also pointing to the need for further research and improved frameworks.